Active packaging with starch, red cabbage extract and sweet whey: Characterization and application in meat. (January 2021) - Ribeiro Sanches, Marcio Augusto; Camelo-Silva, Callebe; da Silva Carvalho, Cleberyanne; Rafael de Mello, Jonatan; Barroso, Noádia Genuario; Lopes da Silva Barros, Eulália; Silva, Paula Paulino; Pertuzatti, Paula Becker
Abstract: Objective: of the study was to evaluate the influence of the concentration of red cabbage extract (RCE) and sweet whey on the properties of starch films using glycerol as plasticizer. The influence of independent variables on the barrier, physical-chemical, mechanical, optical, spectroscopic and antioxidant properties of the films was evaluated. T2 (64.18% RCE and 4.36% sweet whey), T7 (50% RCE and 0.0% sweet whey) and T10 (50% RCE and 15% sweet whey) films presented good mechanical properties, high antioxidant capacity, low solubility and low water vapor permeability, and for that reason they were chosen as treatment that are suitable for use as ground beef packaging. After application as packaging in ground beef, the smallest changes in the quality parameters were noticed in the sample packed with film T2, showing that besides producing an active packaging, the presence of anthocyanins contributes to the conservation of the ground meat. Highlights: Films with properties for application as active packaging in foods were developed. Films showed good mechanical properties, low solubility and water vapor permeability. They also exhibited antioxidant capacity, due to the presence of phenolic compounds. Microscopy showed good structural integrity. Films were able to preserve the quality of ground beef.